Character Education Management in Integrated Dayah An-Nur Bener Meriah Aceh - Andika Hariyanto Surbakti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Character education is an education of values, manners, morals, and character education that aims to develop the ability of students to make good and bad decisions, maintain what is good, and realize goodness in everyday life wholeheartedly. In the context of Islamic education, moral/character education is education regarding the moral foundations and virtues of character traits that children must have and make habits from an early age. Character education has become a global issue, bearing in mind that the nation's children have experienced an alarming moral decline. Forming students with character is not an instant thing. To achieve this, it is necessary to make continuous and continuous efforts. The declaration of character education aims to be one of the solutions to various problems that have been heard, seen, felt, where these problems arise due to the failure of education in instilling moral values ​​in its students. Education does not only produce intelligent individuals, but also must produce individuals with strong character, who are educated through formal and non-formal education, such as schools and Islamic boarding schools.